2007 Florida Plant Disease Management Guide: Apple (Malus sylvestris) - Timur Momol; Laura Ritchie; Hank Dankers (EDIS)
PP 240, a 13-page illustrated fact sheets, describes diseases common to apples in Florida, their symptoms, causal organisms, disease cycles and epidemiology, and management. Includes references and a table of fungicides approved for disease management of apple in Florida. Published by the UF Department of Plant Pathology, October 2007.